Exploring Beyond the Obvious: Social Skills Needed for Agricultural Communication Baccalaureate Graduates - Arthur Leal; Ricky W Telg; Joy N Rumble; Nicole LaMee Perez Stedman; Debbie M. Treise (Journal of Applied Communications, 2019)
This national study sought to expand on current research to identify the importance of and graduates’ ability to perform selected social skills to aid in curricula evaluation and small program development. Using three evaluation groups – agricultural communication graduates, communication industry professionals, and agricultural communication faculty members – 193 individuals responded to the online survey. The most important social skills were those associated with having work values and transitioning into an organization to be a productive member in the workplace. Graduates placed a higher importance on social skills than the other two evaluation groups. All three evaluation groups showed some agreement on graduates’ highest ability to perform several social skills: The ability to be trustworthy, trained, reliable, professional, dedicated, and behave ethically were assigned the highest mean ability. A significant difference was found with the ability graduates afforded themselves in having common sense, being professional, and encompassing maturity versus the other two evaluation groups. Recommendations included incorporating and identifying social skills into instruction for students. Group work, presentations, internships, and student organizations were proposed as opportunities for social skill attainment. Agricultural leadership principles, oral communication, and professional development courses were recommended for new and developing agricultural communication programs that could serve to incorporate the most important social skills. Faculty members could benefit from research that can identify more effective measures to evaluate social skill attainment. Recommendations for future research included a similar assessment with technical skills and for other elements of the Agricultural Communication Program System Model to be assessed.
Keywords: Program evaluation; agricultural communication; agricultural communication program system model; social-skill importance; social-skill ability; three-tiered assessment